Oral manifestation in postmenopausal women of Maharashtra, Western Region - Shrutika Sanjay Muneshwar; S R Ashwinirani; Abhishek Anilrao Gole; Girish Suragimath (Wolters Kluwer Medknow Publications, 2023)
Introduction: Menopause in women is a physiological state that gives rise to adaptive changes at both the systemic and oral levels. The oral manifestations of postmenopausal women may vary for each patient. It occurs in the form of burning mouth syndrome, xerostomia, periodontitis, etc., We aimed to assess the prevalence of oral manifestations in the postmenopausal population, to know the nature and severity of oral manifestations occurring in postmenopausal women, and to assess the systemic conditions of these postmenopausal women with oral manifestations. The study was designed to assess the oral manifestation in postmenopausal women of Maharashtra, Western region. Materials and Methods: The study was conducted in the department of oral medicine and radiology. A total of 90 patients were included. A detailed clinical examination was done using a mouth mirror and probe. The clinical pro forma recorded demographic data, including the duration of menopause and different oral manifestations like xerostomia, periodontitis, lichen planus, oral candidiasis, etc., Collected data were entered into MS Excel and subjected to statistical analysis. Results: In the study, there were a total of 90 patients. These patients were distributed into three groups based on their age groups. The majority of the oral manifestations were reported in patients belonging to Group 2 (60-70 years age group). Conclusion: Overall, 76.6% of patients reported oral mucosal changes; of which 20.2% of patients reported xerostomia, 15.9% reported periodontitis, 13% showed altered taste, 8.6% of patients had lichen planus, and 7.2% patients reported oral candidiasis and space infections.